Burden of rheumatoid arthritis in India from 1990 to 2021: insights from the Global Burden of Disease Database - Shi, Wei; Liang, Xinyu; Zhang, Huafeng; Li, Hui (Frontiers in Medicine, 2025)
ObjectiveRheumatoid arthritis (RA) significantly impacts individual health and society. This study aims to analyze the burden of RA in India from 1990 to 2021 and provide predictions to inform national prevention and control strategies.MethodsUtilizing data from the 2021 Global Burden of Disease (GBD) database, this study describes changes in incidence, prevalence, and disability-adjusted life years (DALY) related to RA in India from 1990 to 2021, while also observing variations across 31 geographical regions.ResultsFrom 1990 to 2021 in India, the incidence, prevalence, and DALY rates of RA showed an increasing trend, with all age-standardized rates being significantly higher in females than in males. The age group of 65–69 years showed the highest incidence rate, while the prevalence peaked at 75–79 years. The forecast results indicate that the age-standardized incidence and DALY rates of RA in India will show an upward trend from 2022 to 2036. There were considerable differences in prevalence across different regions. In 2021, the highest male prevalence was in Uttarakhand, while Goa had the lowest. For females, Tamil Nadu had the highest prevalence, and Madhya Pradesh had the lowest. Overall, areas with high Socio-Demographic Index (SDI) showed a higher disease burden, whereas Kerala, despite a higher SDI, had the lowest burden.ConclusionUsing the GBD database, our findings show that the disease burden of RA in India is on the rise from 1990 to 2021. The prevalence of RA in different regions of India is significantly different, which may be related to local economy and development. The high prevalence of RA in Indian women requires more attention to the early diagnosis and treatment of RA.